Ponatinib Combined With Rapamycin Causes Regression of Murine Venous Malformation. Issue 3 (March 2019) - Li, Xian; Cai, Yuqi; Goines, Jillian; Pastura, Patricia; Brichta, Lars; Lane, Adam; Le Cras, Timothy D.; Boscolo, Elisa
Abstract : Objective—: Venous malformations (VMs) arise from developmental defects of the vasculature and are characterized by massively enlarged and tortuous venous channels. VMs grow commensurately leading to deformity, obstruction of vital structures, bleeding, and pain. Most VMs are associated with the activating mutation L914F in the endothelial cell (EC) tyrosine kinase receptor TIE2. Therapeutic options for VM are limited and ineffective while therapy with the mammalian target of rapamycin inhibitor rapamycin shows moderate efficacy. Here, we investigated novel therapeutic targets promoting VM regression. Approach and Results—: We performed an unbiased screen of Food and Drug Administration–approved drugs in human umbilical vein ECs expressing the TIE2-L914F mutation (HUVEC-TIE2-L914F). Three ABL (Abelson) kinase inhibitors prevented cell proliferation of HUVEC-TIE2-L914F. Moreover, c-ABL, common target of these inhibitors, was highly phosphorylated in HUVEC-TIE2-L914F and VM patient–derived ECs with activating TIE2 mutations. Knockdown of c-ABL/ARG in HUVEC-TIE2-L914F reduced cell proliferation and vascularity of murine VM. Combination treatment with the ABL kinase inhibitor ponatinib and rapamycin caused VM regression in a xenograft model based on injection of HUVEC-TIE2-L914F. A reduced dose of this drug combination was effective in this VM murine model with minimal side effects. The drug combination was antiproliferative, enhanced cell apoptosis and vascular channel regression both in vivo and in a 3-dimensional fibrin gel assay. Conclusions—: This is the first report of a combination therapy with ponatinib and rapamycin promoting regression of VM. Mechanistically, the drug combination enhanced AKT inhibition compared with single drug treatment and reduced PLCγ (phospholipase C) and ERK (extracellular signal-regulated kinase) activity. Abstract : Supplemental Digital Content is available in the text.